Perbandingan Laju Perambatan Retak AL 2024-T3 dan AL 2524-T3 Setelah Mengalami Perlakuan Permukaan. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The objective of this research is to compare the mechanical properties and crack growth rates between Al 2024-T3 and Al 2524-T after being chemically milled and shotpeened processes. First of all, one side of the aluminum surface was chemically milled using NaOH + Na2S +H20 etchant. The surface was then shotpeened with 0, 03A, 0, 05A and 0, 07A peening intensity. The product of chemical milling and shotpeening was tested its hardness, roughness, tensile and crack growth rates. The crack growth test was carried out using a servo hydraulic MTS 810 testing machine under stress level 20% and R= 0,3. The extension of crack length was monitored using two travelling microscopes. Experimental result shows that the fatigue life of chemical milling product decreases about 32% and 22% compared to that of raw materials for Al 2524-T3 and Al 2024-T3, respectively. On the other hand, the fatigue life of shotpeening product increase varying from 85% to 105% compared to that of raw materials. In general, The chemical milling product of Al 2024-T3 has better fatigue life compared to that of Al 2524-T3. In contrast, The shotpeening product of Al 2524-T3 has better fatigue life compared to that of Al 2024-T3.